Analisis Bibliometrik Review: Tren Penelitian Media Pembelajaran Berbasis Digital di Era Gen Z - Sudrajat, Sudrajat (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to identify research trends on digital-based learning media in the Gen Z era and visualize them. The method used is the descriptive bibliometric analysis method. The research data comes from the database dimensions obtained as many as 548 publication articles that have gone through several stages of data collection, namely identification, screening, eligibility, and inclusion. The results of the study concluded that the highest number of publications in 2024 was 227 publication articles. Indonesia is a pair of country bibliographies that have the largest number of documents and have a major influence on the focus of this research compared to other countries. The top-ranked bibliographic pair of institutions/universities is Yogyakarta State University with a total link strength of 61. The pair of journal bibliographies that have the largest number of documents is the science education research journal. The focus of research with the keyword digital-based learning media in the Gen Z era obtained seven clusters. New themes in this field of research are literacy, Islamic education, younger generation, disruption, the industrial revolution era, the society era, and entrepreneurship. These topics can be selected for further research because this topic still rarely appears in research topics.